Evaluation Of Performance Implementation Of Sanitation-Based Community Sanitation Program (SLBM) In Pemalang Regency - Slamet Imam Wahyudi; Soedarsono Soedarsono; Mohamad Anwar (International Conference on Coastal and Delta Areas, 2017)
Sanitation and waste water become an important issue, as population growth. It is estimated that in the next 2025, almost 68.3% of Indonesians inhabit urban areas. Population access to the basic infrastructure of settlements is influenced by aspects of health, environment, socio-cultural education and poverty. Community-Based Environmental Sanitation (SLBM) is one of the sub areas of DAK in the Infrastructure Sector, sourced from the State Budget (APBN) provided to finance sanitation and wastewater activities in regional affairs and become a national priority. Through this research to get: 1) evaluation of program policy toward implementation performance of SLBM, 2) factors influencing performance of SLBM program implementation, 3) dominant factor influencing to SLBM implementation. The research used qualitative quantitative method of quantitative with multiple linear regression analysis. Regression model formed Y = 0.966 + 0.093 X1 + 0.207 X2 + 0.190 X3 + 0.191 X4 + 0.097 X5, where the value of F arithmetic is 36.159 with a significance level of 0.000. The significance level obtained is 0.000 <0.05 so that the regression model is considered feasible to predict the dependent variable (Y) based on the independent variables. Of the five variables tested, community assistance with the coefficient of determination is 32.9% is the dominant variable that affects the success of program implementation performance. The aspect of participation is so important to support the success rate in the development and development of sanitation, therefore the cooperation of all parties between the government and the Sanitation Working Group, the community and all parties is expected to be sustainable. Keywords: Sanitation, SLBM, Community Assistance, Parsitipation.